High magnification carbon nanospheres self-assembled film electrode and preparation method thereof

CN121366877BActive Publication Date: 2026-10-27SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410974346.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2026-10-27
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

[0003]现有的制备碳电极材料方法多是以生物质或者聚合物为前驱体,通过直接碳化法、活化法、硬模板法和软模板法等方法制备,得到的碳材料通常为粉末状,且具有较低的振实密度(0.3~0.7g cm-3),难以获得高体积性能

Benefits of technology

[0029]1、本发明采用蒸发诱导干燥去除了均质海藻酸盐水凝胶中的大孔,得到了致密的海藻酸钠薄膜,然后经催化碳化法制备了密度高达1.18g cm-3的碳薄膜电极;其中50~100nm的碳球作为构建单元相互堆积形成了连续的电子导电网络,同时碳纳米球的自组装结构自发产生了三维离子传输通道,可以用于快速电子/离子传输,进而提高了碳薄膜电极的体积比容量,即实现了紧凑且快速的钠离子存储性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121366877B_ABST
    Figure CN121366877B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high magnification carbon nanospheres self-assembly film electrode and preparation method thereof, comprising the following steps: step one: difficultly soluble calcium salt is added to sodium alginate solution, then add glycollic acid lactone aqueous solution, obtain sodium alginate hydrogel;Step two: sodium alginate hydrogel is evaporated and induced drying, obtain sodium alginate film;Step three: sodium alginate film is soaked in Fe 3+ Solution, crosslinking forms iron alginate film;Step four: iron alginate film is calcined carbonization, after acid washing etching, it is obtained immediately.The application is synthesized dense carbon film electrode with density up to 1.18g cm ‑3 By the densification of self-assembly nanohydrogel film and catalytic graphitization process, which has a density of 1.18g cm-3. These small enough and interlocked nanocarbon spheres (<100 nm) form an interconnected electron-conducting network, while the self-assembly architecture spontaneously generates network topological ion transport channels, which have good energy storage and release capacity for sodium ion storage at high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of material preparation and sodium-ion battery anode application technology, and mainly relates to a high-rate carbon nanosphere self-assembled thin film electrode and its preparation method. Background Technology

[0002] Sodium-ion batteries have attracted increasing attention in sustainable energy storage systems due to their low cost and excellent overall performance. However, anxieties about the limited usage time of portable electronic devices or the limited driving range of electric vehicles are becoming increasingly prominent. To address this issue, there is an urgent need to develop advanced energy storage devices, especially those with both high volumetric energy density and power density, which can help store energy in a smaller space and at a higher rate. Carbonaceous materials are widely considered one of the most promising electrode materials for sodium-ion storage due to their excellent cost-effectiveness and electrochemical activity. Unfortunately, efforts to date on compact carbon-based electrodes appear to be limited.

[0003] Existing methods for preparing carbon electrode materials mostly use biomass or polymers as precursors, employing methods such as direct carbonization, activation, hard template methods, and soft template methods. The resulting carbon materials are typically in powder form and have a low tap density (0.3–0.7 g / cm³). -3 This makes it difficult to achieve high volumetric properties. Furthermore, when used as an electrode material, it requires the assistance of inactive substances (conductive carbon black and binders) in electrode preparation, leading to further reductions in electrode density, increased interparticle resistance, and impeded ion / electron transport. These problems inevitably hinder the full release of the active material Na from the prepared electrode. + Storage capacity. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing dense carbon electrode fabrication technologies and provide a high-rate self-assembled carbon nanosphere thin-film electrode and its fabrication method. The fabrication process is simple, controllable, and low-cost, making it suitable as an electrode material for high-rate sodium-ion batteries. This invention achieves a density as high as 1.18 g / cm³ through a simple and controllable densification and catalytic graphitization process of a self-assembled nanohydrogel film. -3 The carbon nanospheres self-assembled into a dense carbon film (approximately 51.3% of the theoretical density of graphite). These sufficiently small and interlocking carbon nanospheres (<100 nm) formed an interconnected electronic conduction network, while this self-assembly architecture spontaneously generated network topological ion transport channels, thereby achieving compact and fast sodium ion storage performance (107 mAh / cm³). -3 @50Ag -1 ).

[0005] The objective of this invention can be achieved through the following process:

[0006] In a first aspect, the present invention provides a method for preparing a high-ratio carbon nanosphere self-assembled thin film electrode, comprising the following steps:

[0007] Step 1: Add sparingly soluble calcium salt to sodium alginate solution, then add glucono-delta-lactone aqueous solution to obtain sodium alginate hydrogel;

[0008] Step 2: Evaporate-induced drying of sodium alginate hydrogel to obtain sodium alginate film;

[0009] Step 3: Immerse the sodium alginate film in Fe 3+ In solution, cross-linking forms an iron alginate film;

[0010] Step 4: The iron alginate film is calcined and carbonized, and then acid-etched to obtain the final product.

[0011] As one embodiment of the present invention, in step one, the sparingly soluble calcium salt includes either nano-CaCO3 suspension or nano-CaSO4 suspension.

[0012] In one embodiment of the present invention, in step one, the mass ratio of sparingly soluble calcium salt, gluconolactone and sodium alginate is 5-7:7-9:40.

[0013] In some preferred embodiments, the mass concentration of the nano-CaCO3 suspension is 0.5-0.7 wt.%, the mass concentration of the glucono-delta-lactone aqueous solution is 0.7-0.9 wt.%, and the mass concentration of the sodium alginate solution is 1.8-2.2 wt.%.

[0014] In one embodiment of the present invention, in step one, the sparingly soluble calcium salt is added to the sodium alginate solution and then stirred. Thorough stirring ensures that the sparingly soluble calcium salt nanoparticles are uniformly dispersed between the sodium alginate segments. Since the sparingly soluble calcium salt nanoparticles are not hydrolyzed, the resulting mixture remains a fluid solution.

[0015] In one embodiment of the present invention, in step one, after adding the glucono-delta-lactone aqueous solution, ultrasonic treatment is performed, followed by settling and standing. The purpose of ultrasonic treatment is to eliminate air bubbles.

[0016] This invention utilizes the weak acidity of gluconolactone to lower the pH of the mixed solution, thereby controlling the hydrolysis of sparingly soluble calcium salt nanoparticles and slowly releasing Ca. 2+ This allows sodium alginate to react with uniformly dispersed Ca. 2+ In-situ spontaneous cross-linking yields homogeneous bulk sodium alginate hydrogels. In contrast, traditional methods involve directly adding sodium alginate to a metal ion solution, resulting in excessively rapid cross-linking and typically producing heterogeneous hydrogels that are difficult to form the smooth sodium alginate films required later.

[0017] In one embodiment of the present invention, in step two, the temperature for evaporation-induced drying is 20-40°C, and the time is 20-30 hours. Evaporation-induced drying uses a forced-air drying oven. If the temperature is too low, the drying time will be prolonged; if the temperature is too high, the moisture will evaporate too quickly, causing the film to wrinkle.

[0018] This invention employs an evaporation-induced drying process that removes water and macropores from large sodium alginate hydrogels. Capillary forces promote the tight stacking of loosely distributed alginate chains, ultimately forming a smooth, homogeneous sodium alginate film with excellent mechanical properties, which can serve as a precursor for the subsequent preparation of dense carbon films. In contrast, freeze-drying hydrogels only yields brittle and porous alginate aerogels, which are difficult to further form dense derived carbon materials and cannot form thin-film electrodes.

[0019] As one embodiment of the present invention, in step three, Fe 3+ The solution concentration was 0.08-0.15 mol / L, and the crosslinking time was 20-30 h. Since metal ions typically affect the microstructure of alginate-derived carbon materials, Fe was selected here. 3+ The purpose of using iron as a crosslinking ion is to take advantage of the low-temperature catalytic graphitization properties of iron, which helps the transformation of alginate-derived carbon in the carbonization process.

[0020] In some preferred embodiments, the Fe 3+ The solvent used in the solution includes a mixture of deionized water and ethanol in a volume ratio of 10:1-3. The Fe... 3+ The solution includes one of Fe(NO3)3, FeCl3, and Fe2(SO4)3.

[0021] In one embodiment of the present invention, in step four, the calcination and carbonization involves heating to 750-850°C at a rate of 4-6°C / min and holding at that temperature for 0.5-1 h. During the carbonization process, Fe atoms can catalyze the rearrangement of amorphous carbon atoms to form a graphite structure, which possesses high electrical conductivity (38.6 S cm⁻¹). -1 ).

[0022] Furthermore, the calcination and carbonization are carried out under an inert atmosphere with a flow rate of 0.6-0.8 L / min.

[0023] In some preferred embodiments, the calcination carbonization process includes: calcining an iron alginate film sandwiched between two pieces of quartz glass under an inert atmosphere, with the inert atmosphere flowing at a rate of 0.6-0.8 L / min; the calcination carbonization temperature is 780-830℃, the heating rate is 4-6℃ / min, and the time is 0.5-3 h. Using quartz glass allows for the application of pressure to the polymer film, preventing structural bending caused by weight loss during high-temperature carbonization, thus ensuring that the resulting carbonized product maintains a flat film morphology and possesses a certain degree of flexibility.

[0024] In one embodiment of the present invention, in step four, the acid solution used for pickling and etching includes 1.8-2 mol / L hydrochloric acid, the pickling and etching temperature is 90-110℃, and the time is 20-30 h. The pickling and etching removes Fe3C.

[0025] In one embodiment of the present invention, in step four, after acid etching, the material is cleaned (to neutrality) and vacuum dried to obtain a carbon nanosphere self-assembled thin film electrode; the vacuum drying temperature is 100-110℃ and the time is 20-30h.

[0026] Compared to sodium alginate crosslinked Fe 3+ Regarding the carbon aerogel powder obtained through freeze-drying and carbonization processes, the dense carbon film obtained by the present invention can simultaneously possess high electrode density and abundant ion transport channels, and can be directly used as an electrode.

[0027] Secondly, the present invention provides a high-ratio carbon nanosphere self-assembled thin film electrode obtained by the preparation method described above.

[0028] Compared with the prior art, the advantages of the present invention are as follows:

[0029] 1. This invention uses evaporation-induced drying to remove macropores in homogeneous alginate hydrogels, obtaining dense sodium alginate films, which are then prepared by catalytic carbonization to achieve a density as high as 1.18 g / cm³. -3 The carbon thin film electrode consists of carbon nanospheres of 50–100 nm that are stacked together to form a continuous electronically conductive network. At the same time, the self-assembled structure of the carbon nanospheres spontaneously generates a three-dimensional ion transport channel, which can be used for rapid electron / ion transport, thereby improving the volumetric capacity of the carbon thin film electrode and achieving compact and fast sodium ion storage performance.

[0030] 2. The carbon thin film prepared by this invention can be used directly as an electrode without the need to introduce other low-density inert components for auxiliary electrode assembly, such as conductive agents and binders. This will further improve the continuous conductivity and volumetric energy density (i.e., volumetric specific capacity) of the electrode.

[0031] 3. The raw materials used in this invention are readily available, the preparation method is simple, the process is easy to control, and the cost is low, making it a promising candidate for application in the field of sodium-ion batteries. Attached Figure Description

[0032] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:

[0033] Figure 1 An optical photograph of the homogeneous sodium alginate hydrogel prepared in Example 1;

[0034] Figure 2 Scanning electron microscope image of the carbon nanosphere self-assembled thin film electrode prepared in Example 1;

[0035] Figure 3 X-ray diffraction pattern of the carbon nanosphere self-assembled thin film electrode prepared in Example 1;

[0036] Figure 4 The N2 adsorption / desorption isotherm and pore size distribution of the carbon nanosphere self-assembled thin film electrode prepared in Example 1 are shown.

[0037] Figure 5 The rate performance diagram of the carbon nanosphere self-assembled thin film electrode prepared in Example 1 as a sodium ion anode material is shown.

[0038] Figure 6 The sodium ion diffusion coefficient diagram is shown for the self-assembled thin film electrode of carbon nanospheres prepared in Example 1.

[0039] Figure 7 Rate performance diagrams of the carbon nanosphere self-assembled thin film electrodes prepared in Examples 2 and 3 when used as sodium ion anode materials;

[0040] Figure 8 An optical photograph of the heterogeneous sodium alginate hydrogel prepared for Comparative Example 1;

[0041] Figure 9 An optical photograph of the iron alginate aerogel prepared in Comparative Example 2;

[0042] Figure 10 Scanning electron microscope image of the porous carbon aerogel powder prepared in Comparative Example 2;

[0043] Figure 11 The rate performance of the porous carbon powder-based electrode prepared in Comparative Example 2 as a sodium-ion anode material is shown in the figure.

[0044] Figure 12 The sodium ion diffusion coefficient diagram of the porous carbon powder-based electrode prepared for Comparative Example 2. Detailed Implementation

[0045] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, providing detailed implementation methods and specific operating procedures, which will help those skilled in the art to further understand the present invention. It should be noted that the scope of protection of the present invention is not limited to the following embodiments; any adjustments and improvements made under the concept of the present invention are all within the scope of protection of the present invention.

[0046] Example 1

[0047] Step 1: Dissolve 1.0g of sodium alginate in 50ml of deionized water and stir thoroughly for 48h to obtain a 2wt.% sodium alginate solution.

[0048] Step 2: Weigh 0.15g of calcium carbonate and 0.20g of gluconolactone and add them to 25ml of deionized water. Sonicate and stir to form a 0.6wt.% CaCO3 suspension and a 0.8wt.% gluconolactone solution.

[0049] Step 3: Add the solution prepared in Step 2 to the solution prepared in Step 1, stir magnetically until homogeneous, and then sonicate for 20 seconds to remove air bubbles.

[0050] Step 4: Immediately transfer the gel to a 3mm deep culture dish for slow ionic crosslinking. After standing for 24 hours, a homogeneous sodium alginate hydrogel with excellent mechanical strength is obtained. Place the obtained hydrogel on a clean, flat glass plate and dry it in a 30℃ forced-air drying oven for 24 hours to obtain a dense sodium alginate film.

[0051] Step 5: Weigh 5.40g of FeCl3·6H2O and dissolve it in 200ml of a 10:3 mixture of deionized water and ethanol. Immerse the sodium alginate film in the prepared 0.1mol / L FeCl3·6H2O solution for ionic crosslinking for 24 hours. Then, wash the fully crosslinked polymer film with deionized water and allow it to air dry to obtain a uniform and smooth iron alginate film.

[0052] Step 6: The (orange-red) iron alginate film obtained in Step 5 is sandwiched between two flat quartz glasses to form a sandwich structure. It is then transferred to a tube furnace and calcined at 800℃ for 0.5h under an Ar atmosphere with a flow rate of 0.7L / min and a heating rate of 5℃ / min. The resulting iron carbide / carbon composite material is obtained after carbonization.

[0053] Step 7: Immerse the carbonized product obtained in Step 6 in 300 mL of 2 mol / L hydrochloric acid solution and perform thorough acid washing at 100°C for 25 h to remove iron carbide.

[0054] Step 8: Wash with deionized water until pH=7, then transfer to a vacuum drying oven at 110℃ and dry thoroughly for 24 hours to obtain the sodium alginate-derived carbon nanosphere self-assembled thin film electrode.

[0055] Figure 1 This is an optical photograph of the homogeneous sodium alginate hydrogel obtained in step four of this embodiment.

[0056] Figure 2 The image shows a scanning electron microscope image of the carbon nanosphere self-assembled thin film electrode obtained in this embodiment. As can be seen from the image, the thickness of the thin film electrode is about 21 μm, and it is self-assembled from carbon nanospheres with a diameter of 50 to 100 nm. This self-assembled configuration spontaneously forms a three-dimensional continuous electron / ion transport network.

[0057] Figure 3 The image shows the X-ray diffraction pattern of the carbon nanosphere self-assembled thin film electrode obtained in this embodiment. As can be seen from the image, the (002) peak contains a broad peak of ~22° and a shoulder peak of ~26°. This asymmetric peak shape indicates that the carbon exists in a form that changes from an amorphous state to a graphitic state.

[0058] Figure 4 The figures show the N2 adsorption / desorption isotherms and pore size distribution of the carbon nanosphere self-assembled thin film electrode obtained in this embodiment; as shown in the figures, the BET specific surface area of ​​the carbon film is 229 m². 2 g -1 The total pore volume is 0.302 cm³. 3 g -1 Furthermore, the pore size is widely distributed in the mesoporous range of 4–50 nm.

[0059] Figure 5 The graph shows the rate performance of the carbon nanosphere self-assembled thin film electrode obtained in this embodiment as a sodium ion anode material; as shown in the graph, the density of the thin film electrode is 1.18 g / cm³. -3 At 0.05Ag -1 At low current densities, the average volumetric specific capacity of the thin-film electrode is 214.2 mAh cm⁻¹. -3 As current density increases, the specific capacity decays more slowly, even at 50Ag. -1 Even at ultra-high current densities, the thin-film electrode can still retain 107 mAh cm⁻¹. -3 High volumetric capacity.

[0060] Figure 6 The figure shows the sodium ion diffusion coefficient of the self-assembled thin film electrode of carbon nanospheres obtained in this embodiment; as can be seen from the figure, its sodium ion diffusion coefficient is 2.53*10. -9 ~1.12*10 -8 cm 2 s -1 .

[0061] The electrochemical testing conditions are as follows: A 2032-type button cell was assembled using the thin-film electrode obtained in this embodiment as the working electrode, a sodium metal sheet as the reference electrode and counter electrode, 1M NaPF6 (diethylene glycol dimethyl ether, DEGDME) as the electrolyte, and Whatman GF / D glass fiber as the separator. The rate performance of the electrode was obtained by performing galvanostatic charge-discharge (GCD) tests at different current densities at room temperature. The sodium ion diffusion coefficient was measured using galvanostatic intermittent titration (GITT). Specifically, before the test, the sodium ion half-cell was heated to 0.05Ag… -1 The battery was charged and discharged three times at a given current density, followed by a periodic test of 10 minutes of discharge / charge followed by 50 minutes of rest. Both GCD and GITT tests were performed on a LAND CT2001A battery testing system, with a test voltage window of 0.01–2.5V vs. Na. + / Na.

[0062] Example 2

[0063] Step 1: Dissolve 1.0g of sodium alginate in 50ml of deionized water and stir thoroughly for 48h to obtain a 2wt.% sodium alginate solution.

[0064] Step 2: Weigh 0.15g of calcium carbonate and 0.20g of gluconolactone and add them to 25ml of deionized water. Sonicate and stir to form a 0.6wt.% CaCO3 suspension and a 0.8wt.% gluconolactone solution.

[0065] Step 3: Add the solution prepared in Step 2 to the solution prepared in Step 1, stir magnetically until homogeneous, and then sonicate for 20 seconds to remove air bubbles.

[0066] Step 4: Immediately transfer the gel to a 3mm deep culture dish for slow ionic crosslinking. After standing for 24 hours, a homogeneous sodium alginate hydrogel with excellent mechanical strength is obtained. Place the obtained hydrogel on a clean, flat glass plate and dry it in a 30℃ forced-air drying oven for 24 hours to obtain a dense sodium alginate film.

[0067] Step 5: Weigh 5.40g of FeCl3·6H2O and dissolve it in 200ml of a mixed solution of deionized water and ethanol (volume ratio 10:3). Immerse the membrane in the prepared 0.1mol / L FeCl3·6H2O solution for ionic crosslinking for 24 hours. Then, wash the fully crosslinked polymer membrane with deionized water and allow it to air dry to obtain a uniform and smooth iron alginate membrane.

[0068] Step 6: The (orange-red) iron alginate film obtained in Step 5 is sandwiched between two flat quartz glasses to form a sandwich structure. It is then transferred to a tube furnace and calcined at 700℃ for 0.5h under an Ar atmosphere with a flow rate of 0.8L / min and a heating rate of 4℃ / min. The resulting iron carbide / carbon composite material is obtained after carbonization.

[0069] Step 7: Immerse the carbonized product obtained in Step 6 in 300 mL of 2 mol / L hydrochloric acid solution and perform thorough acid washing at 100°C for 30 h to remove iron carbide.

[0070] Step 8: Wash with deionized water until pH=7, then transfer to a vacuum drying oven at 110℃ and dry thoroughly for 24 hours to obtain the sodium alginate-derived carbon nanosphere self-assembled thin film electrode.

[0071] Example 3

[0072] Step 1: Dissolve 1.0g of sodium alginate in 50ml of deionized water and stir thoroughly for 48h to obtain a 2wt.% sodium alginate solution.

[0073] Step 2: Weigh 0.15g of calcium carbonate and 0.20g of gluconolactone and add them to 25ml of deionized water. Sonicate and stir to form a 0.6wt.% CaCO3 suspension and a 0.8wt.% gluconolactone solution.

[0074] Step 3: Add the solution prepared in Step 2 to the solution prepared in Step 1, stir magnetically until homogeneous, and then sonicate for 20 seconds to remove air bubbles.

[0075] Step 4: Immediately transfer the gel to a 3mm deep culture dish for slow ionic crosslinking. After standing for 24 hours, a homogeneous sodium alginate hydrogel with excellent mechanical strength is obtained. Place the obtained hydrogel on a clean, flat glass plate and dry it in a 30℃ forced-air drying oven for 24 hours to obtain a dense sodium alginate film.

[0076] Step 5: Weigh 5.40g of FeCl3·6H2O and dissolve it in 200ml of a mixed solution of deionized water and ethanol (volume ratio 10:3). Immerse the membrane in the prepared 0.1mol / L FeCl3·6H2O solution for ionic crosslinking for 24 hours. Then, wash the fully crosslinked polymer membrane with deionized water and allow it to air dry to obtain a uniform and smooth iron alginate membrane.

[0077] Step 6: The (orange-red) iron alginate film obtained in Step 5 is sandwiched between two flat quartz glasses to form a sandwich structure. It is then transferred to a tube furnace and calcined at 850°C for 1 hour under an Ar atmosphere with a flow rate of 0.6 L / min and a heating rate of 6°C / min. The resulting iron carbide / carbon composite material is obtained after carbonization.

[0078] Step 7: Immerse the carbonized product obtained in Step 6 in 300 mL of 2 mol / L hydrochloric acid solution and perform thorough acid washing at 100°C for 20 h to remove iron carbide.

[0079] Step 8: Wash with deionized water until pH=7, then transfer to a vacuum drying oven at 110℃ and dry thoroughly for 24 hours to obtain the sodium alginate-derived carbon nanosphere self-assembled thin film electrode.

[0080] Figure 7 The graph shows the rate performance of the carbon nanosphere self-assembled thin film electrodes obtained in Examples 2 and 3 as sodium ion anode materials; as can be seen from the graph, the densities of the thin film electrodes obtained in Examples 2 and 3 are 1.15 g / cm³, respectively. -3 1.20g cm -3 Under the same test conditions as in Example 1, the thin-film electrode was tested at 0.05 A g. -1 The average volumetric specific capacity at the current density was 194.5 and 189.1 mAh cm⁻¹, respectively. -3 Furthermore, as the current density increases, the specific capacity decays more slowly, exhibiting excellent volumetric specific capacity and rate performance.

[0081] Comparative Example 1

[0082] The preparation method of this comparative example is basically the same as that of Example 1, except that the calcium source is replaced by an aqueous solution of CaCl2 instead of a suspension of sparingly soluble calcium salts such as CaCO3.

[0083] Specifically, in step two, weigh 0.15g of calcium chloride and add it to 25ml of deionized water, then sonicate and stir to form a 0.6wt.% CaCl2 solution. In step three, transfer the sodium alginate solution obtained in step one to a 3mm high petri dish and add the CaCl2 aqueous solution prepared in step two; or directly pour the sodium alginate solution obtained in step one into the CaCl2 aqueous solution. In step four, let it stand for 12 hours to allow the sodium alginate to react with the CaCl2. 2+ Fully cross-linked.

[0084] The hydrogel obtained in this comparative example has a heterogeneous structure. (See attached...) Figure 8 As shown, where Figure 8 a is an optical photograph of the hydrogel obtained by adding CaCl2 solution to sodium alginate solution. Figure 8b is an optical photograph of the hydrogel obtained by adding sodium alginate solution to CaCl2 solution. Due to the presence of sodium alginate and CaCl2 in the aqueous solution... 2+ The rapid cross-linking of the hydrogels resulted in a heterogeneous structure in which a sodium alginate solution was wrapped by a calcium alginate surface, making it unsuitable for preparing dense sodium alginate films.

[0085] Comparative Example 2

[0086] The preparation method of this comparative example is basically the same as that of Example 1, except that the homogeneous hydrogel obtained in step four is directly immersed in the prepared Fe... 3+ Ionic cross-linking occurs in the solution, followed by freeze-drying to remove moisture.

[0087] Specifically, in step four, the gel was immediately transferred to a 3 mm high culture dish for slow ionic crosslinking. After standing for 24 hours, a homogeneous sodium alginate hydrogel with excellent mechanical strength was obtained. In step five, 5.40 g of FeCl3·6H2O was weighed and dissolved in 200 ml of a 10:3 mixture of deionized water and ethanol. The homogeneous hydrogel obtained in step four was then directly immersed in the prepared 0.1 mol / L FeCl3·6H2O solution for ionic crosslinking for 24 hours. After washing with deionized water, it was freeze-dried at -60°C and 1 Pa for 24 hours.

[0088] The hydrogel obtained in this comparative example is a brittle and porous iron alginate aerogel, such as... Figure 9 As shown. The product obtained after carbonization and acid washing is porous carbon powder, such as... Figure 10 As shown.

[0089] The porous carbon powder sample (80 mg) obtained in this comparative example was mixed with commercial conductive carbon black and binder (polyvinylidene fluoride dissolved in N-methylpyrrolidone, 0.025 g / ml). -1 The mixture was prepared by mixing the powders in a mass ratio of 8:1:1 and stirring thoroughly to form a slurry. This slurry was then coated onto copper foil and vacuum-dried at 110°C for 12 hours. The resulting porous carbon powder-based electrode sheet was then cut into pieces using a 12mm diameter slicer. Based on the electrode sheet loading and thickness, its electrode density was calculated to be 0.51 g / cm³. -3 This is much smaller than the density of the thin-film electrode obtained in the examples (1.15–1.20 g / cm³). -3 ).

[0090] Figure 11 The graph shows the rate performance of the porous carbon powder-based electrode obtained in this comparative example as a sodium-ion anode material. As can be seen from the graph, under the same test conditions as in Example 1, the obtained porous carbon powder-based electrode exhibits good rate performance at 0.05 and 5 A g. -1The average volumetric capacity at current density is only 87.7 and 55.4 mAh cm⁻¹. -3 The electrochemical performance of the thin film electrodes obtained in Examples 1, 2, and 3 is significantly lower than that of the thin film electrodes obtained in Examples 1, 2, and 3.

[0091] Figure 12 The figure shows the sodium ion diffusion coefficient of the porous carbon powder-based electrode obtained in this comparative example; as can be seen from the figure, its sodium ion diffusion coefficient is 9.85*10. -10 ~5.38*10 -9 cm 2 s -1 .

[0092] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a high-ratio carbon nanosphere self-assembled thin-film electrode, characterized in that, Includes the following steps: Step 1: Add sparingly soluble calcium salt to sodium alginate solution, then add glucono-delta-lactone aqueous solution to obtain sodium alginate hydrogel; The sparingly soluble calcium salt includes either nano-CaCO3 suspension or nano-CaSO4 suspension. Step 2: Evaporate-induced drying of sodium alginate hydrogel to obtain sodium alginate film; Step 3: Immerse the sodium alginate film in Fe 3+ In solution, cross-linking forms an iron alginate film; Step 4: The iron alginate film is calcined and carbonized, and then acid-etched to obtain the final product.

2. The preparation method according to claim 1, characterized in that, In step one, the mass ratio of sparingly soluble calcium salt, gluconolactone, and sodium alginate is 5-7:7-9:

40.

3. The preparation method according to claim 1, characterized in that, In step two, the temperature for evaporation-induced drying is 20-40 ℃, and the time is 20-30 h.

4. The preparation method according to claim 1, characterized in that, In step three, the Fe 3+ The solution contains one of Fe(NO3)3, FeCl3, and Fe2(SO4)3; the Fe 3+ The concentration of the solution is 0.08-0.15 mol / L.

5. The preparation method according to claim 1, characterized in that, In step three, the cross-linking time is 20-30 hours.

6. The preparation method according to claim 1, characterized in that, In step four, calcination and carbonization involves heating to 750-850℃ at a rate of 4-6℃ / min and holding at that temperature for 0.5-1 h.

7. The preparation method according to claim 1, characterized in that, In step four, the acid solution used for pickling and etching includes 1.8-2 mol / L hydrochloric acid, the pickling and etching temperature is 90-110 ℃, and the time is 20-30 h.

8. The preparation method according to claim 1, characterized in that, In step four, after acid etching, the material is cleaned and vacuum dried to obtain a carbon nanosphere self-assembled thin film electrode; the vacuum drying temperature is 100-110 ℃ and the time is 20-30 h.

9. A high-ratio carbon nanosphere self-assembled thin film electrode obtained by the preparation method according to any one of claims 1-8.

Citation Information

Patent Citations

  • Electrodes for energy storage devices

    CA3270984A1

  • Composite electrode material, preparation method thereof and application of material

    CN108039465A